2019
DOI: 10.1021/acsaem.9b00331
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Synthesis and Performance of Fe-Based PGM-Free Catalysts in Acidic and Alkaline Media: Evolution of Surface Chemistry and Morphology

Abstract: The effects of the synthesis steps of a platinum group metal-free (PGM-free) catalyst on the surface chemistry, morphology, and electrochemical activity in acidic and alkaline media toward the oxygen reduction reaction (ORR) were studied. Each step exhibits a positive impact on catalyst activity. In acid media, etching of the silica template is the major contributor to the enhancement of the half-wave potential, as the ORR active sites formed during the first pyrolysis become more accessible. Further processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…In order to produce such catalysts there are two different pathways, a template-based and a carbon support-based synthesis. Silica [ 8 ] or quite complex and expensive metal-organic-frameworks (MOFs) [ 9 ] can be used as a template, whereas for the support-based synthesis commercial carbon blacks [ 7 , 10 ] are utilized. The latter approach has the advantage of a simple and cheap synthesis without the requirement of a template removing step and the targeted use of carbon material with known morphology, porosity, surface area, and functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…In order to produce such catalysts there are two different pathways, a template-based and a carbon support-based synthesis. Silica [ 8 ] or quite complex and expensive metal-organic-frameworks (MOFs) [ 9 ] can be used as a template, whereas for the support-based synthesis commercial carbon blacks [ 7 , 10 ] are utilized. The latter approach has the advantage of a simple and cheap synthesis without the requirement of a template removing step and the targeted use of carbon material with known morphology, porosity, surface area, and functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The initial preparation conditions for the electrocatalysts such as mixing of different waste plastics percentage, homogenization of the sample, grounding the precursors to a fine powder should be the subject of extended studies. Moreover, process parameters such as pyrolysis temperature, atmosphere, heating and cooling rates must be studied and optimized to obtain a controlled and defined morphology and surface chemistry [126,127] . For doping and surface functionalization, the role of precursors choice could be an important research topic [128] .…”
Section: Discussionmentioning
confidence: 99%
“…The samples were further subjected to a pyrolysis treatment to overcome a possible heterogeneity in porosity and modification in surface chemistry induced by ball-milling, which may have contributed to decrease the active site utilization [59]. The pyrolysis step after ball-milling led to an increase in ECSA only for the sample prepared with no ball-milling (146 m 2 g −1 for FeNC_P vs. 19 m 2 g −1 for FeNC) and the sample obtained with 1 h of ball-milling time (69 m 2 g −1 for FeNC_BM1_P vs. 54 m 2 g −1 for FeNC_BM1).…”
Section: Samplementioning
confidence: 99%
“…Atanassov and coworkers demonstrated that a ball-mill treatment followed by pyrolysis induced a decrease in relative amount of both mesopores and macropores homogenizing morphology of Fe-N-C catalysts. In an alkaline environment, these materials directly catalysed oxygen reduction to water, with a reduction potential of 0.93 V vs. RHE [59].…”
Section: Contextualization Into Existing Literaturementioning
confidence: 99%